Acetylcholinesterase and Butyrylcholinesterase Inhibitory Activity of Extracts from Medicinal Plants - Talić, Stanislava; Dragičević, Ivan; Ćorajević, Lejla; Martinović Bevanda, Anita (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE), enzymes which breakdown acetylcholine and butyrylcholine, are considered as a promising strategy for the treatment of Alzheimer’s disease(AD). A potential source of AChE and BuChE inhibitors is provided by the abundance of plants in nature. In the present study, we selected five plants used in traditional medicine to treat different disorders of the central nervous system.Aqueous and methanolic extracts of sage (Salvia officinalis L.), arnica (Arnica montana L.),rue (Ruta graveolens L.), St. John'swort(Hypericum perforatumL.) and aronia (Aroniamelanocarpa(Michx.) Elliot.)were tested for the AChE and BuChE inhibitory activity using Ellman’s colorimetric method. Galanthamine hydrobromide was used as positive control. The results show that extracts from the aeiral parts of St John's wort and rue and flowers of arnica could inhibit the activity of AChE or BuChE or both. The best inhibition effect was observed using the water extract of rue, then methanolic extracts of arnicaand StJohn'swort at concentration of 400 μg ml-1.